2019
DOI: 10.13181/mji.v28i2.2687
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sensitivity of several anticancer drugs in TMEPAI knockout triple-negative breast cancer cells

Abstract: BACKGROUND Transmembrane prostate androgen-induced protein (TMEPAI) was reported to be highly amplified in the majority of patients with triple-negative breast cancer (TNBC). TMEPAI is related to poorer prognosis, limited treatment options, and prone to drug resistance compared with other proteins. One of the established markers to determine cancer resistance to drugs is the increased expression levels of drug efflux transporters. However, the role of TMEPAI in cancer resistance to drugs has not been elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“… 33 , 34 A previous study by Wardhani et al reported that without TGF-β stimulation, the response of TNBC Hs578T to cytotoxic drugs would be reversed. 35 In our study, doxorubicin retained its cytotoxic effect result in both TMEPAI positive and negative cells. Nonetheless, TMEPAI knock-out cells showed a more potent result.…”
Section: Discussionsupporting
confidence: 57%
“… 33 , 34 A previous study by Wardhani et al reported that without TGF-β stimulation, the response of TNBC Hs578T to cytotoxic drugs would be reversed. 35 In our study, doxorubicin retained its cytotoxic effect result in both TMEPAI positive and negative cells. Nonetheless, TMEPAI knock-out cells showed a more potent result.…”
Section: Discussionsupporting
confidence: 57%
“…In the absence of TGF-β, wild-type TNBC cells were more sensitive to cytotoxic than the KO-cells, followed by a decrease in drug efflux transporters, P-gp, and BCRP expressions. 38 Therefore, we suggest that the effect of TMEPAI on the change in cell response to anticancer is highly dependent on TGF-β.…”
Section: Discussionmentioning
confidence: 89%
“…18,36,37 In our previous study, we reported that in TNBC-KO, a higher dose of doxorubicin, paclitaxel, and cisplatin as compared to wild type, which is in contrast with our present result. 38 TMEPAI-KO cells showed decreased sensitivity to several chemotherapy drugs. In this system, TGF-β was not used to induce TMEPAI.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation